Sedimentological characteristics of storm-induced washover deposits along the coastal zone of Changwat Prachuap Khiri Khan to Nakhon Sri Thammarat, Thailand - Sumet Phantuwongraj (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2012